Geochemistry of Noble Gases and CO2 in Fluid Inclusions From Lithospheric Mantle Beneath Wilcza Góra (Lower Silesia, Southwest Poland) - Rizzo, Andrea Luca; Pelorosso, Beatrice; Coltorti, Massimo; Ntaflos, Theodoros; Bonadiman, Costanza; Matusiak-Małek, Magdalena; Italiano, Francesco; Bergonzoni, Giovanni (Frontiers in Earth Science, 2018)
Knowledge of the products originating from the subcontinental lithospheric mantle (SCLM) is crucial for constraining the geochemical features and evolution of the mantle. This study investigated the chemistry and isotope composition (noble gases and CO2) of fluid inclusions (FI) from selected mantle xenoliths originating from Wilcza Góra (Lower Silesia, southwest Poland), with the aim of integrating their petrography and mineral chemistry. Mantle xenoliths are mostly harzburgites and sometimes bear amphiboles, and are brought to the surface by intraplate alkaline basalts that erupted outside the north-easternmost part of the Eger (Ohře) Rift in Lower Silesia. Olivine (Ol) is classified into two groups based on its forsterite content: (1) Fo88.9–91.5, which accounts for a fertile-to-residual mantle, and (2) Fo85.5–88.1, which indicates large interactions with circulating (basic) melts. This dichotomy is also related to orthopyroxene (Opx) and clinopyroxene (Cpx), which show two ranges of Mg# values (87–90 and 91–93, respectively) and clear evidence of recrystallization. CO2 predominates within FI, followed by N2. The δ13C of mantle CO2 varies between –4.7‰ and –3.1‰, which mostly spans the MORB range (−8‰ < δ13C < −4‰). The 3He/4He ratio is 6.7–6.9 Ra in Cpx, 6.3–6.8 Ra in Opx, and 5.9–6.2 Ra in Ol. These values are within the range proposed for European SCLM (6.3±0.3 Ra). The decrease in 3He/4He from Cpx to Ol is decoupled from the He concentration, and excludes any diffusive fractionation from FI. The chemistry of FI entrapped in Ol indicates that the mantle is depleted by variable extents of partial melting, while that of Opx and Cpx suggests the overprinting of at least one metasomatic event. According to Matusiak-Małek et al. (2017), Cpx, Opx, and amphiboles were added to the original harzburgite by carbonated hydrous silicate melt related to Cenozoic volcanism. This process resulted in entrapment of CO2-rich inclusions whose chemical and isotope composition resembles that of metasomatizing fluids. We argue that FI data reflect a mixing between two endmembers: (1) the residual mantle, resulting from partial melting of European SCLM, and (2) the metasomatic agent, which is strongly He-depleted and characterized by MORB-like features.